ANALISIS KETERAMPILAN MENJUAL ANEKA KERAJINAN DAN PAKAIAN KHAS KOTA POTIANAK PADA TOKO RAUDAH COLECTION - Rusdiana Nengsih; F.Y. Khosmas; Bambang Genjik S (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe title of the research is the an analysis of skills in selling various handicrafts and typical Pontianak  clothes in the RAUDAH  Collection store. The aims to know the skills of selling various handicrafts and clothing typical of Pontianak city in the RAUDAH Collection shop. The method used in this research is using a qualitative method of the research approach. The data sources in this research are the leaders and employees of the RAUDAH Collection shop, which amounted to two people. The data collection techniques are live observation techniques, interviews, and documentary study techniques. The data collection tools are interview guidelines, observation sheets (checklists). The data processing techniques use reduction analysis, presentation, and verification. The results of the findings based on observation data and interviews in the study concluded that the problem in the skills of selling the education that is owned not from the secondary school, but the high school And no training for employees of the Raudah Collection shopKeywords: Selling skills, miscellaneous crafts, typical clothes Pontianak city